A study of atherogenic index of plasma in myocardial infarction patients admitted in Silchar medical college, Assam, India - Choudhury, Biswadeep; Chakraborty, Manidip; Karim, Nabiha Mayanaz (International Journal of Research in Medical Sciences, 2021)
Background:It is an established fact that dyslipidemia is one of the major risk factors for cardiovascular diseases like myocardial infarction. Major well-known alterations in lipid profile include high serum cholesterol, low density lipoprotein cholesterol (LDL-C), triglyceride and low high density lipoprotein cholesterol (HDL-C). Recently, it has been found that atherogenic index of plasma (AIP); which is a logarithmically transformed ratio of triglyceride and HDL-C; can predict cardio-vascular disease risk and can also be used for cardio-vascular disease risk stratification. In this study we have calculated the AIP from fasting lipid profile of patients suffering from myocardial infarction and tried to assess the correlation between AIP and myocardial infarction. Methods: The study comprised of fifty patients suffering from myocardial infarction aged more than 18 with no prior history of cardiovascular diseases. We measured fasting lipid profile using Vitros 5600 full auto analyzer and calculated AIP using online AIP calculator. Statistical analysis was done using “Microsoft excel 2019” with add on. A significant percentage (66%) of myocardial infarction patients had higher AIP (>0.21) and fell in the high-risk group. We also got a significant relationship between AIP-triglyceride and AIP-HDL-C (p<0.05 considered as statistically significant). Conclusions: AIP is high in myocardial infarction patients. In this group, besides high AIP, they also have low HDL-C and high triglycerides which are significant. So, AIP can be used as a tool for cardio-vascular disease risk stratification.